Little Man, Little Man : A Story of Childhood - Baldwin, James, 1924-1987 (Book collections on Project MUSE., 2018)
Now available for the first time in nearly forty years, James Baldwin's only children's book Little Man, Little Man follows the day to day life of the four year old protagonist TJ and his friends in their 1970s Harlem neighborhood as they encounter the social realities of being black in America.